PENGARUH PELATIHAN KARYAWAN TERHADAP KINERJA KARYAWAN PADA CV CIBALUNG HAPPY LAND BOGOR - Yusnita, Nancy; Fadhil, Feriza (JIMFE (Jurnal Ilmiah Manajemen Fakultas Ekonomi), 2015)
ABSTRACTThe one of Factors affecting the performance of the employees is training. Training is a very important operational activities within the company. The quality of employees can be developed in the training itself. To produce employees who have the skills and knowledge appropriate mental attitude with which the company takes delivery of training is a must. Through the training will improve employee performance that can support a companys success. The analytical method used is descriptive qualitative, the analysis used is the correlation coefficient, determination coefficient, simple linear regression analysis, hypothesis testing of correlation and regression hypothesis testing. Results of the study revealed that the fact of implementation of employee training and employee performance in CV Cibalung Happy Land Bogor pretty good. The hypothesis test results is a real relationship between employee training and employee performance. Results of regression hypothesis test can be concluded that the training effect on performance. Positive t value means a positive effect, namely if the training climb performance will increase.Keywords: employee training, employee performanceÂ